2007
DOI: 10.1021/ja0650293
|View full text |Cite
|
Sign up to set email alerts
|

TiIV-Mediated Reactions between Primary Amines and Secondary Carboxamides:  Amidine Formation Versus Transamidation

Abstract: Titanium(IV)-mediated reactions between primary amines and secondary carboxamides exhibit different outcomes, amidine formation versus transamidation, depending on the identity of the TiIV complex used and the reaction conditions employed. The present study probes the origin of this divergent behavior. We find that stoichiometric TiIV, either Cp*TiIV complexes or Ti(NMe2)4, promotes formation of amidine and oxotitanium products. Under catalytic conditions, however, the outcome depends on the identity of the Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…[44] Interestingly, in this case the reactions with aniline as the nucleophile were particularly efficient. [45,48] We have reported that B(OCH 2 CF 3 ) 3 is an effective reagent for the transamidation of primary amides to secondary amides (Scheme 20). [45,48] We have reported that B(OCH 2 CF 3 ) 3 is an effective reagent for the transamidation of primary amides to secondary amides (Scheme 20).…”
Section: Transamidation Reactionsmentioning
confidence: 99%
“…[44] Interestingly, in this case the reactions with aniline as the nucleophile were particularly efficient. [45,48] We have reported that B(OCH 2 CF 3 ) 3 is an effective reagent for the transamidation of primary amides to secondary amides (Scheme 20). [45,48] We have reported that B(OCH 2 CF 3 ) 3 is an effective reagent for the transamidation of primary amides to secondary amides (Scheme 20).…”
Section: Transamidation Reactionsmentioning
confidence: 99%
“…Several metal complexes have been reported to promote transamidation reactions in the last two decades, including AlCl 3, 7 Sc(OTf) 3 ,8 Ti(NMe 2 ) 4 9 and polymer‐bound HfCl 4 10. Lanthanide catalysts have been reported to promote transamidation between Fmoc protected lactams and various amines 11.…”
Section: Screen Of Catalystsmentioning
confidence: 99%
“…There are several reports of thermal transamidation reactions, [4] typically requiring very high temperatures (> 180 8C), thus having a very limited substrate range. The use of the yeast Candidia cylindracea lipase has been reported by Gotor et al to promote transamidations between Ntrifluoroethyl-2-chloropropionamide and various amines [5] and intramolecular transamidations have been reported by Langlois and Buchwald et al [6] Several metal complexes have been reported to promote transamidation reactions in the last two decades, including AlCl 3, [7] Sc(OTf) 3 , [8] Ti(NMe 2 ) 4 [9] and polymer-bound HfCl 4 . [10] Lanthanide catalysts have been reported to promote transamidation between Fmoc protected lactams and various amines.…”
mentioning
confidence: 99%